Steudnera hoanglienica (Colocasieae—Araceae), a new species from northern Vietnam - Du, Nguyen Van; Quang, Bui Hong; Tien, Tran Van; Bogner, Josef (Phytotaxa, 2018)
Steudnera hoanglienica is described as a new species from Lai Chau province of Vietnam. The characters of the new species are compared with the three known closely related species in Indochina.